Branching Response of Poinsettia ‘Orange Spice’ to a Combination of Pinching, No Pinching, and Atrimmec - Bruce L. Dunn (American Society for Horticultural Science (ASHS), 2021)
This study aimed to identify the best method to improve poor branching of poinsettia ‘Orange Spice’. Treatments included pinched and unpinched alone and in combination with four different rates (3.9, 7.8, 11.7, and 23.4 mL⋅L−1) of Atrimmec. Pinching reduced plant height, as did unpinched + 11.7 mL⋅L−1 and unpinched + 11.7 mL⋅L−1 Atrimmec. Neither pinching nor Atrimmec had any effect on plant width, stem caliper, or shoot dry weight. Atrimmec did not increase the number of laterals in combination for pinched or unpinched treatments, but unpinched plants generally produced more laterals. Unpinched with any rate of Atrimmec resulted in tertiary shoots, which improved the visual appearance and quality.